Influence of pH and ionic strength on the antibacterial effect of hyaluronic acid/chitosan films assembled layer-by-layer. (December 2018) - Nascimento, Vicente; França, Carla; Hernández-Montelongo, Jacobo; Machado, Daisy; Lancellotti, Marcelo; Cotta, Mônica; Landers, Richard; Beppu, Marisa
Graphical abstract: Highlights: HA/CHI films were assembled by LbL at different pH and IS conditions of synthesis. Films at optimized conditions presented high antibacterial effect against S. aureus . The antibacterial effect was higher when the number of bilayers was increased. Abstract: Hyaluronic acid (HA)/chitosan (CHI) films were assembled by LbL using different conditions of pH and ionic strength (IS) in order to obtain stable surfaces to avoid the adhesion and proliferation of Pseudomonas aeruginosa and Staphylococcus aureus . The results showed that pH and IS were key synthesis variables for obtaining different features, such as wettability, thickness and the availability of functional groups. The antibacterial effect was more effective against S. aureus with a reduction of approximately 3, 4, and 1.5 log reduction after 4, 8 and 24 h of culture time, respectively. In the case of P. aeruginosa, the films presented a lower bacterial reduction: 1 log reduction in times evaluated. In conclusion, the results of the antibacterial effect against S. aureus after 24 h, suggest that the HA/CHI films assembled by LbL can protect several substrates, such as biomedical devices, against bacterial proliferation.